Attacking embedded systems through fault injection - Sastry, J K R; Bhanu, J S; SubbaRao, K (2011 2nd National Conference on Emerging Trends and Applications in Computer Science, 2011)
Embedded Systems are being used for the development and implementation of Safety and Mission Critical Systems. Malfunctions of such type of embedded systems will lead to disasters at times. The embedded systems must be fully secured from outside intervention in order to have effective functioning as well as to provide protective environment to these mission critical systems. Fault injection attacks are one kind of side channel attacks that affect embedded systems by injecting a fault into the system. There are several kinds of Fault injection attacks that can affect the security of the embedded systems. The kind of side channel attacks that can be induced into embedded systems are dependent on the hardware used and the Applications Software implemented on such hardware. There are several attacking systems discussed in the literature each requiring a kind of counter attacking systems. Most of the attacking systems are not supported by experimental setups. Experimental setups are required as many samples of attacks are to be carried and then the attacking system is proved using the output generated by the application of samples. In this paper, an experimental setup is proposed, using which, the Embedded System can be attacked by the usage of several samples of data through conducting the variations in the supply voltages. The experimental set-up explores theconcept of latch up effect for attacking. A safety critical system for monitoring and controlling of the temperatures within nuclear Reactor System is designed and exposed to the attacking experimental setup. The experimental system is tested using the simulation and the experimental results are published.